Nazis after Hitler : how perpetrators of the Holocaust cheated justice and truth - McKale, Donald M. 1943- (Rowman & Littlefield, 2012)
1. World War II and allied promises -- 2. Four faces of genocide : what happened in the war : Franz Stangl : camp commandant -- Dr. Werner Best : the administrator -- Erich von dem Bach-Zelewski : commander of killing units -- Walther Rauff : mass murderer by bullets and gas vans -- 3. Leaving Auschwitz : First postwar reports -- Josef Mengele : healer turned killer -- Irma Grese : beautiful sadist -- Mengele : imprisoned and released by the Americans -- Wilhelm Boger : the interrogator -- 4. A liberation of contrasts : Best and the Danish Jews -- Josef Kramer : "beast of Belsen" -- Best imprisoned in Copenhagen -- 5. Soviet "liberators" : The war and postwar tragedy of Soviet Jewry -- Reports and trials -- Bernhard Bechler : denazification director -- Karl Clauberg : Aushwitz doctor -- 6. In the custody of leniency : Stangl : doubt in Trieste -- Hermann Göring : prize prisoner -- Kurt Daluege : uniformed policeman -- Stangl : escaping an Austrian prison -- Karl Wolff : the allies' favorite -- Heinrich Himmler : suicide -- Stangl : Linz, Rome, and Damascus -- 7. Nuremberg, number two, and the substitute : Best as defense witness -- Otto Ohlendorf's admission of "innocence" -- Göring : a troublesome number two -- Ernst Kaltenbrunner : the stand-in? -- Best : from self-importance to self-pity -- 8. Nuremberg : "King Frank" : Hitler's lawyer -- The "butcher of Poland" -- Capture in Germany -- Trial by diary -- 9. Nuremberg : "Fred" the "endowed seer" and verdicts and sentences : "Innocent" Ideologue? -- "Innocent" Visionary? -- Racist murderer -- "Innocence" on trial -- Verdicts and sentences -- Justice evaded (Göring), justice enacted (Kaltenbrunner, Rosenberg, and Frank) -- 10. Poland : occasional trials amid a continuing Holocaust : Rising tide of hate -- A papal appeal for Arthur Greiser -- The pogrom -- Amon Goeth : a court's rare admission -- Rudolf Höss : trial of the death dealer -- Other trials -- 11. Memory in West Germany : long and short : Nazi hunter in the making -- A "family history" -- Alfred Ebner's real past -- West German "justice" -- Ebner : a typical example -- 12. Pseudo-purges and politics : Denazification -- Karl Löffler : Cologne's gestapo chief -- Hermann Josef Abs : the "non-Nazi" banker -- Dr. Ernst Buchner : art thief -- 13. Other trials and amnesty : Ohlendorf accuses the victims -- Franz Schlegelberger : daggar beneath his robe -- The Danish verdicts on Best -- The Dutch verdict on Hanns Albin Rauter -- Robert Wagner : a French verdict -- Erich von Manstein : long delayed British "justice" -- Best : freedom amid allied and other pardons -- 14. Eichmann, Jerusalem, and Eichmann's henchmen : Aliases of evil -- Capture -- Trial and execution -- Eichmann's men : Alois Brunner ; Franz Novak -- 15. Hunting the comfortable : The happy Stangle couple -- Mengele : from freedom to an accidental death -- The tightening noose around Stangl -- Klaus Barbie : a U.S. Cold War spy -- Stangl's arrest -- 16. Four faces long after the war : what didn't happen : Stangl : finally the accused -- Best eludes punishment -- Bach-Zelewski : nothing to hide? -- Walther Rauff : no remorse in Chile -- 17. The post-Holocaust world